Effects of focal muscle vibration on cervical pain in Parkinson's disease patients: a pilot study - Gianpaolo Ronconi; Dario Mattia Gatto; Mariantonietta Ariani; Sefora Codazza; Maurizio Panunzio; Daniele Coraci; Paola Emilia Ferrara (PAGEPress Publications, 2024)
Musculoskeletal pain is a common symptom of Parkinson's disease (PD) that is not adequately treated with current dopaminergic drugs. This pilot study sought to investigate the effect of focal muscle vibration (fMV) on a group of Parkinson's disease patients suffering from chronic cervical pain. In addition to conventional physiotherapy, twenty-two patients with idiopathic Parkinson's disease (Hoehn and Yahr stages II-III) received three weeks of bilateral focal musclevibration to the trapezius muscles. The Visual Analogue Scale (VAS), the Short-form McGill, and the Present PainIntensity scales were used to assess pain at baseline (T0), after three weeks of treatment (T1), one week after the last treatment session (T2), and three weeks after T2 (T3). Pain intensity decreased significantly from baseline to T1 across all pain scales (p < 0.0001). Furthermore, the beneficial effect of fMV on cervical pain lasted up to one month after treatment. Our findings show that fMV, in combination with conventional physiotherapy, is effective at reducing pain intensity in PD patients, with results visible even after a month of follow-up.